STRESS LEVELS IN FOOTBALL REFEREES (Fiep Bulletin - online, 2025)
The present study aimed to analyze the stress level of football referees in the State of Rio de Janeiro. This study is field-based, descriptive and quantitative. Ten football referees from different sporting levels participated in the study. The instrument for data collection was the Stress Test for Referees (TEPA). The results showed that the main factors causing stress were: disorganized competition, being aware after the game of the mistake made; making mistakes in the last decisive minutes; arriving late or late at the game venue; lack of recognition and/or appreciation. We conclude that the perception of stress of the referees analyzed comes from the relationship with the environment and people in the work environment (social factor) and from the mental relationships of the situation on the field (psychological factor).
Keywords: Stress; Referee; Soccer